Obveznost postavitve vprašanj za predhodno odločanje s strani Vrhovnega sodišča - Kerševan, Erik (Pravnik, 2023)
The preliminary ruling procedure before the Court of Justice of the European Union (CJEU) is one of the main mechanisms for ensuring the uniform application of European Union law. The article examines how the Supreme Court, as the highest court in the country, deals with issues of application of European Union law at various stages of the revision process and how is this consideration reflected in case law with a focus on administrative dispute cases. The article discusses the latest developments in case law (and open questions), also taking into account the recent precedential judgement of the CJEU in the case C-561/19 Consorzio Italian Management of 6 October 2021. It also highlights dilemmas and concerns raised by the recent decision of the Constitutional Court in the case Up-1133/18 of 31 March 2022. In its decision the Constitutional Court instructs the Supreme Court, in cases where revisions are not admissible, to give reasons as to why it did not refer a case for a preliminary ruling based on a party’s motion. According to the existing established Supreme Court case law, a preliminary question cannot be referred to the CJEU in the decision-making process on the admissibility of revision. The article represents the point of view that in the given circumstances the decision of the Supreme Court to refer a preliminary question to the CJEU regarding the compatibility of the existing regulation of admissibility of revision with the requirements of European Union law was well founded.
Keywords: pravo EU; predhodno odločanje; revizija; revizijski postopek; Sodišče Evropske unije; upravni spor; ustavna sodišča; vrhovna sodišča